Joint Leisure Time, Communication, and Marital Satisfaction among Taxi Drivers - Clara Alverina Rhenardo; Jenny Lukito Setiawan (Universitas Ciputra Surabaya, 2017)
This study aims to examine the relationship between joint leisure time, as well as communication, and marital satisfaction among taxi drivers. The subjects included in this study were 87 taxi drivers (100% male) in company X Surabaya. Quantitative method in this research is used with correlational design. Incidental sampling was used as the sampling technique. Instruments used in this study were joint leisure time scale (Kurniawan & Setiawan, 2016), communication scale (Olson & Larson, 2008), and marital satisfaction scale (Grable & Britt, 2006). The result of multiple correlation test shows that there is a positive relationship between joint leisure time and communication altogether with marital satisfaction (R=0.673; ρ<0.05). The result of partial correlation test shows that there is a relationship between joint leisure time and marital satisfaction by controlling communication (r=0.497; ρ<0.05). The results also shows that there is a relationship between communication and marital satisfaction by controlling joint leisure time (r=0.441; ρ<0.05). Based on the results above it can be concluded that joint leisure time and communication altogether (R2=45.2%) gives higher contribution to marital satisfaction compared to joint leisure time and communication being separated. In addition, joint leisure time (r2=32%) contributed better with marital satisfaction compared to communication (r2=13.2%).Keywords: Communication, joint leisure time, marital satisfaction, taxi driver